2021
DOI: 10.1038/s41598-021-03568-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal childhood trauma and perinatal distress are related to infants’ focused attention from 6 to 18 months

Abstract: Maternal distress is repeatedly reported to have negative impacts on the cognitive development in children and is linked to neurodevelopmental disorders (e.g. attention-deficit/hyperactivity disorder and autism spectrum disorder). However, studies examining the associations between maternal distress and the development of attention in infancy are few. This study investigated the longitudinal relationships between maternal distress (depressive symptoms, anxiety symptoms, and exposure to childhood trauma) and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 123 publications
0
16
0
Order By: Relevance
“…Child outcomes were categorized into six domains: infant/toddler development, child physical/physiological problems, child mental health problems, child internalizing and externalizing problems, child temperament, and child academic performance. Fifteen studies (22.1%) assessed the effects of parental ACEs on infant and toddler developmental outcomes, mainly including four areas: fine and gross motor skills, speech and language development, cognitive development and problem solving, and social-emotional development (Brittain et al, 2021; Chang et al, 2020; Choi et al, 2017; Coe et al, 2020; Folger et al, 2018; Garon-Bissonnette et al, 2022; McDonnell et al, 2016; Miccoli et al, 2022; Racine et al, 2018; Riggs et al, 2022; Sun et al, 2017; Treat et al, 2019; Tu et al, 2021; Wurster et al, 2020; Zhang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Child outcomes were categorized into six domains: infant/toddler development, child physical/physiological problems, child mental health problems, child internalizing and externalizing problems, child temperament, and child academic performance. Fifteen studies (22.1%) assessed the effects of parental ACEs on infant and toddler developmental outcomes, mainly including four areas: fine and gross motor skills, speech and language development, cognitive development and problem solving, and social-emotional development (Brittain et al, 2021; Chang et al, 2020; Choi et al, 2017; Coe et al, 2020; Folger et al, 2018; Garon-Bissonnette et al, 2022; McDonnell et al, 2016; Miccoli et al, 2022; Racine et al, 2018; Riggs et al, 2022; Sun et al, 2017; Treat et al, 2019; Tu et al, 2021; Wurster et al, 2020; Zhang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Bouvette et al (2013) reported that child attachment security moderated the association between maternal adversity and child temperament, and Hatch et al (2020) found that maternal ACEs were only associated with children’s externalizing behaviors in the presence of low family social support. Other scholars revealed that parent hostile/helpless state of mind (Sauvé et al, 2022), parental emotional availability (Wurster et al, 2020), and maternal anxiety (Tu et al, 2021) all moderated the relationship between parental ACEs and child negative health outcomes. However, Wang et al (2022) indicated that parental role had no moderation effect on the association between parental ACEs and child behavioral problems and functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach, which spans intersections of gender, age, and culture, requires arts and health professionals to respect and hold space for multiple aspects of diversity including gender fluidity and expansive cultural understandings of human spirituality and wellbeing beyond physical health (Eckersley, 2007;Wobcke, 2015). Doing so, responds to growing evidence of the intergenerational effects of mothers' childhood and during-pregnancy-trauma on their babies and children (Tu, Skalkidou, Lindskog & Gredebäck, 2021). Edwards (2017) argued for creative arts therapy professionals to adopt trauma informed approaches to working with all people.…”
Section: Discussionmentioning
confidence: 99%
“… Note. This figure is reprinted from “Maternal Childhood Trauma and Perinatal Distress Are Related to Infants’ Focused Attention From 6 to 18 Months,” by H. F. Tu, A. Skalkidou, M. Lindskog, and G. Gredebäck, 2021, Scientific Reports, 11 (1) (https://doi.org/10.1038/s41598-021-03568-2).…”
mentioning
confidence: 99%